"Mick - Mick - you've suffered enough - " [Bob Hawke, Mick Young] - Pryor, Geoff, 1944- (1983)
Mick Young is brought back into the Government fold after his suspension from the Hawke Ministry for an indiscretion revealed in the Hope Royal Inquiry into the Combe-Ivanov affair. David Combe, a Labor stalwart of old (former National Secretary of the Labor Party) is not so lucky. He is considered to have acted naively in allowing himself to be duchessed by a KGB agent (Ivanov), and is cast into the political outlands.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 7 December 1983.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Hawke, Bob, -- 1929-2019 -- Caricatures and cartoons; Young, Mick, -- 1936-1996 -- Caricatures and cartoons; Prime ministers -- Australia -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons; Federal politicians